Employees' perceptions of trade unions in unionised companies: A survey in Malaysia. - Che Rose, Raduan; Ramasamy, Nagiah; Kumar , Naresh (2010)
This paper contributes to the understanding of barriers to trade unionism in Malaysia by analysing the perspectives of employees from unionised companies. Employees' perceptions are somewhat positive about their job and work environment and these could be a factor in explaining their non-membership in unions. The survey analysis revealed that non-union employees do not view their unions favourably and perhaps it raises doubts among employees on the ability of unions to protect workplace issues critical to workers. Conceivably this is an indictment of the ineffectiveness of trade unions' leadership. The instrumental perspective appears very prominently in the struggles of unions, and to a lesser extent, the political/ideological perspective. Employees seem to lack knowledge concerning trade unions, indicating unions' failure to reach out to the broad workforce and it is a possible problem in union organising. Union officials should pay more attention to communicating their union's unique characteristics and impact at the workplace. It also offers opportunities to trade unionists to convince the non-union employees in unionised companies for collective representation.